Editorial Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Yahaya, Mohammad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza; Nazrin, Nizar (Idealogy Journal; Vol 3 No 1 (2018): Idealogy Journal (April 2018)DO - 10.24191/idealogy.v3i1.280, 2018)
We are very pleased that IDEALOGY JOURNAL, Journal of Arts and Social Science is presenting its 3rd volume and 1st issue. We are also very excited that the journal has been attracting papers from a variety of advanced and emerging countries such as Indonesia, Pakistan, Saudi Arabia, Bangladesh, etc. The variety of submissions from such countries will help the aimed global initiatives of the journal.